Kualitas Sumberdaya Manusia dalam Pelayanan Administrasi Kependudukan di Kabupaten Buton Selatan - Zainul Abidin; Asmiddin Asmiddin; Nurhayati Nurhayati; La Kali (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article intends to describe the quality of the human resources of the apparatus in population administration services in South Buton Regency. Research data obtained by interview, observation and study of documentation and analyzed by means of qualitative inductive inference process and analysis of the dynamics of the relationship between the observed phenomena. This research concludes, the quality of human resources of the apparatus in population administration services in Sampolawa District, South Buton Regency is quite good, the development is carried out by involving employees through employee education and training that has been carried out, although the employees involved are still limited to pre-service training and are only followed by ASN. Employees are motivated in providing public services, but the provision of rewards and incentives and disincentives to employees is still very limited, the discipline of some employees needs to be improved. Career development is open to every employee, but promotion and placement are the authority of the Regional Personnel Agency of South Buton Regency